2015
DOI: 10.1038/hdy.2014.124
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of muscle between hybrid abalone and parental lines Haliotis gigantea Reeve and Haliotis discus hannai Ino

Abstract: To understand the potential molecular mechanism of heterosis, protein expression patterns were compared from hybrids of Haliotis gigantea (G) and Haliotis discus hannai (D) using two-dimensional gel electrophoresis (2-DE) and matrix-assisted laser desorption/ionization time-of-flight/time-of-flight analyses. Expression differences were observed in muscle samples from the four groups with 673 ± 21.0 stained spots for H. discus hannai ♀ × H. discus hannai ♂ (DD), 692 ± 25.6 for H. gigantea ♀ × H. gigantea ♂ (GG)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 35 publications
2
11
0
Order By: Relevance
“…Given that each protein extraction method has its own bias in extracting proteins; it is not surprising that a substantial amount of differing protein spots were found between the gels from the two methods. A study using TRIzol extraction demonstrated approximately 700 protein spots on the 2-DE gel of fresh abalone muscle [ 35 ]. However, only approximately 200 protein spots were obtained from the dried abalone sample in the current study ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that each protein extraction method has its own bias in extracting proteins; it is not surprising that a substantial amount of differing protein spots were found between the gels from the two methods. A study using TRIzol extraction demonstrated approximately 700 protein spots on the 2-DE gel of fresh abalone muscle [ 35 ]. However, only approximately 200 protein spots were obtained from the dried abalone sample in the current study ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The TRIzol-based extraction method was first applied successfully on halophilic protein samples for the generation of 2-DE in 2006 [ 19 ]. This protein extraction method has subsequently been widely used in 2-DE for a wide range of samples, including rat spinal cord [ 20 ], human/animal cell lines [ 21 , 22 , 23 ], dinoflagellates [ 11 , 24 , 25 , 26 , 27 , 28 ], mites [ 29 ], plant tissue [ 30 ], clinical samples [ 31 , 32 , 33 ], marine animals [ 34 , 35 , 36 ], and reef corals [ 37 ] ( Table 1 ). This TRIzol-based method has gained popularity for 2-DE because it offers several advantages [ 19 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Protein extractions were performed using TRIzol-mediated sample preparation as described previously (Di et al 2013(Di et al , 2015. The protein pellet was air-dried and resuspended in isoelectric focusing (IEF) redissolving buffer [7 M of urea, 2 M of thiourea, 4% (w/v) CHAPS, 40 mM of Tris].…”
Section: Extraction Of Abalone Egg Proteinsmentioning
confidence: 99%
“…Protein identification was carried out as previously described (Di et al 2013(Di et al , 2015. Briefly, spots of interest were excised and trypsin digested trypsin, with 0.5 lL of extracted sample analyzed by matrix-assisted laser desorption/ionization time-of-flight/time-of-flight (MALDI-TOF/TOF) with a 5800 Proteomics Analyzer (Applied Biosystems, CA, USA).…”
Section: Protein Identification By Mass Spectrometrymentioning
confidence: 99%